Single-Dose Intravenous Simvastatin Treatment Attenuates Renal Injury in an Experimental Model of Ischemia-Reperfusion in the Rat - Zorica Nešic; Zoran Todorovic; Radan Stojanovic; Gordana Basta-Jovanovic; Sanja Radojevic-Škodric; Ruzica Velickovic; Prabal K. Chatterjee; Christoph Thiemermann; Milica Prostran (Elsevier, 2006)
The effect of acute pretreatment with a single dose of simvastatin (1 mg/kg, i.v.; 30 min before ischemia) on renal dysfunction caused by ischemia-reperfusion (I/R) injury in the rat was investigated. I/R injury was induced by clamping both renal vascular pedicles for 45 min, followed by 4 h of reperfusion with saline (2 ml/kg per hour). Simvastatin significantly improved both parameters of glomerular and tubular dysfunction (e.g., creatinine levels and fractional excretion of Na+, respectively) and especially improved the histological score, compared to control I/R-injured rats treated with saline or 10% DMSO only. Keywords:: simvastatin, ischemia-reperfusion renal injury, acute renal failure